Microbiota composition and intestinal integrity remain unaltered after the inclusion of hydrolysed Nannochloropsis gaditana in Sparus aurata diet - Cerezo Ortega, Isabel M.; Di Zeo-Sánchez, Daniel Enrique; García-Márquez, Jorge; Ruiz Jarabo, Ignacio; Sáez-Casado, M.I.; Balebona-Accino, María del Carmen; Moriñigo-Gutiérrez, Miguel Ángel; Tapia-Paniagua, Silvana Teresa (Springer Nature, 2021)
The use of lysed microalgae in the diet of carnivorous fish can increase the bioavailability of proteins and bioactive compounds, such as unsaturated fatty acids or vitamins in the digestive tract. These are essential molecules for the proper physiological development of fish in aquaculture. However, some antinutritional components and other undesirable molecules can be released from an excess of microalgae supplied, compromising the integrity of the intestine. The inclusion of small amounts of hydrolized microalgae in the fish diet can be a good strategy to avoid negative effects, improving the availability of beneficial compounds. Nannochloropsis gaditana is an interesting microalgae as it contains nutraceuticals. Previous studies reported beneficial effects after its inclusion in the diet of Sparus aurata, a widely cultured species in Europe and in all Mediterranean countries. However, administration of raw microalgae can produce intestinal inflammation, increased intestinal permeability, bacterial translocation and disturbance of digestion and absorption processes.
Keywords: Peces - Alimentación; Sparus aurata; Nannochloropsis gaditana; Functional diet